THE ROLE OF LEADER IN IMPROVING EMPLOYEE PERFORMANCE ASSESSMENT AT PT SIIX EMS INDONESIA PURCHASING SECTION - Rifkiana Mariska; Budi Rismayadi; Neni Sumarni (SEAN Institute, 2022)
The purpose of this study was to determine the role of leadership in improving employee performance appraisal. In particular, this research has a target to (1) analyze how the process of implementing the leadership role in improving performance appraisal, (2) analyzing the supporting and inhibiting factors in the implementation of the leadership role in improving performance appraisal of employees of PT. SIIX EMS Indonesia Purchasing section. This type of research is qualitative using a case study approach. Data collection techniques used by means of observation, interviews, documentation. The data obtained were validated through: a) Persistence of observation, b) Triangulation of Data Sources, c) Adequacy of Reference. The research data is processed through the following techniques: a) Data Reduction, b) Data Presentation, c) Conclusion Drawing, which aims to obtain data to support the final results of the study. The results show that the fair dimension has not gone well, because managers in providing performance appraisals based on proximity to employees are not in accordance with KPI standards, dimensions support goals, managers in supporting work adjust to company conditions so that teamwork between employees goes well, dimensions being appreciative, managers give awards to employees who excel, but in providing performance appraisals they still use the element of closeness to employees